Pengembangan Sensor untuk Mendeteksi Kesegaran Buah Durian (Durio zibethinus Murr.) Kupas Berbasis Indikator Alami Ekstrak Kayu Secang (Caesalpinia sappan L.) - Nur Alfi Syahrin; Bambang Kuswandi; Lestyo Wulandari (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Durian is a famous native fruit from Southeast Asia and usually sold within durian-cut packaging in the supermarket because it is handy and ready to serve. However, its freshness level is unknown. Sensor, made by sappanwood decoct extract, can be used to detect the fruit freshness within the packaging. The aim of this research was to develop a sensor to detect cut durian freshness based on natural indicators from sappanwood extract. Indicator solution of sappanwood decoction consist of sappanwood decoct extract, phosphate buffer pH 7,5 and polyvinyl alcohol (PVA). The color change from sensor was examined by ImageJ software to get mean red. Durian pulp was examined every day to get pH and SSC (Solid Soluable Concentration) value in for 5 days of storage at room temperature. The result of rotten pulp durian was showed by the color-changing of the sensor from red purplish to yellow with mean red 224,215 ± 0,161. Durian pulp freshness in room temperature decreased as the pH decreased from 7,46 to 4,20 and as the SSC decreased from 7,60 to 2,40, followed by the color-changing of the sensor. Furthermore, the level of durian pulp freshness can be detected by freshness sensor based on natural indicators from sappanwood extract at room temperature storage.